Multiple Intelligences dalam Al-Qur’an serta Implikasinya dalam Pendidikan Islam - Alam, Aden Aang Umar; Aziz, Jamil Abdul; Han, Muhamad Ibtissam (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2023)
This research aims to change the old paradigm, that in fact there are many, multidimensional, intelligences in every human being who lives on this earth. It also aims to analyze the verses of the Qur'an relating to the multiple intelligences. The type of research used in this research is library research. Data sources consist of two types, namely primary data and secondary data. This study uses data collection techniques in the form of documentation. The analytical approach uses an interpretive perspective approach. Meanwhile, data analysis used content analysis method. Test the validity of the data using the credibility of the data. The results of the study show that each discussion of multiple intelligences can be found in the Qur'an; mathematical-logical intelligence is in Q.S Ali-Imran[3]: 190-191, language/linguistic intelligence is in Q.S Ar-Rahman[55]: 1-4, interpersonal intelligence is in Q.S Al-Hujurat: 13, intrapersonal intelligence is in Q.S Al-Isra'[17]: 36, and naturalist intelligence is in Q.S Al-Qashas[28]: 77. Furthermore, mathematical-logical intelligence, language/linguistic intelligence and intrapersonal intelligence enter the realm of nature in relation to Islamic education . Meanwhile interpersonal intelligence and naturalist intelligence belong to morals in relation to Islamic education. Meanwhile, the relevance of the concept of multiple intelligences to Islamic education can be seen from how Allah bestows various kinds of gifts of intelligence on His servants, not just one. The goal is to help people solve the problems that exist in their lives.